A phenomenological comparison of the effects of blue light, red light and radio waves on the escape speed of Caenorhabditis elegans and the rate of closure of Gerbera jamesonii petals - Alexander W. Kline; Charles S. Beattie; Addison K. Shenk; Samuel I. Spicher; Timothy A. Bloss; Laura Tipton; Marquis T. Walker; Laura G. Vallier; Kristopher L. Schmidt; Giovanna Scarel (PLoS ONE, 2026)
Objective Great interest surrounds understanding the effects of radio waves on biological organisms, including humans, animals and plants. Several prior studies, however, showed contradictory results. We hypothesized that the problem lay in the lack of a method for evaluating the energy transferred from radio waves, or electromagnetic waves in general, to biological organisms. Therefore, we proposed to measure the transferred energy with the classic electromagnetic wave energy, i.e., the product of the intensity and the inverse of the frequency of the waves. Methods To test this hypothesis, we exposed two simple light-sensitive biological organisms, Caenorhabditis elegans ( C. elegans ) and Gerbera jamesonii ( G. jamesonii ), to radio waves, red light, blue light and white light. We selected frequency and intensity such that each type of electromagnetic wave could transfer a similar amount of energy to the biological organisms. We then observed the kinematic and postural response of C. elegans , and the rate of closure of G. jamesonii ’s petals to assess whether similar effects would be detected when the energy at different frequencies is similar. Conclusions In both C. elegans and G. jamesonii , we found that radio waves trigger effects like those generated by light with similar energy. This outcome provides support to our hypothesis. We therefore infer that electromagnetic wave intensity needs to be considered when estimating possible harm linked to the exposure of biological organisms to radio waves or, in general, electromagnetic waves. Moreover, the successful ability of radio waves in biological organisms to produce effects like those produced by blue light, together with their long penetration depth in tissues, stimulates the investigation of radio waves as a substitute for blue light in a non-invasive version of optogenetics.